Hormonal And Clinical Monitoring Of Postpartum Ovarian Function In Surti Buffaloes - Shah, R.G.; Dhami, A.J.; Kavani , F.S. (Indian Journal of Veterinary Sciences and Biotechnology, 2012)
The hormonal (P4 and E2) profile and ovarian changes of 39 postpartum Surti buffaloes were studied at weekly interval from calving to at least 91 days postpartum with a view to characterise the ovarian function. The profile of both P4 and E2 hormones showed sequential biweekly trend. As against calving, the mean plasma progesterone concentration was significantly higher (4.39 ± 0.67 vs 1.19 ± 0.33 ng/ml) and that of estradiol was lower (6.77 ± 1.39 vs 153.05 ± 21.74 pg/ml) by 13-16 weeks postpartum. A total of 70 ovulations were monitored through steroids profile, which showed fertile oestrus as 55.72 %, silent ovulation 17.14%, anovulation 5.14%, unserved oestrus 5.71%, and early embryonic death 15.71%, which also included the long luteal phase. The non conceived animals had a combined pattern of delayed rise and low level of progesterone during luteal phase indicative of insufficient luteal function than that of conceived animals, which had normal progesterone profile. The fluctuations observed in 17ß estradiol levels during early postpartum period were non-specific and erratic. The rising level of 17ß estradiol was associated with folliculogenesis as evident by rectal palpation prior to first heat postpartum.